Public Policy Making - ANDERSON, James E (Houghton Mifflin Company, 2006)
To explain the fundamentals of public policy, this best-selling text focuses on the process behind the crafting of legislation. By examining the individual steps--from identifying a problem, to agenda setting, to evaluation, revision, or termination of a policy--students are able to see how different factors influence the creation of policy. Each chapter features at least one case study that illustrates how general ideas are applied to specific policy issues. This new Seventh Edition addresses the economic crisis as well as how the Obama administration differs from the Bush administration in its approach to policy making.